OPTIMASI SEDIAAN TRANSDERMAL PATCH NATRIUM DIKLOFENAK TIPE MATRIKS - Hendradi, Esti; Isnaeni, .; Fridayanti, Aditya; Pujianti, Efrin (Jurnal Farmasi Indonesia, 2011)
The study was designed to investigate the optimation of preparation of transdermal patch sodium diclofenac matrix type. In this study, matrix-type base containing diclofenac sodium were prepared using polymeric combination of EC N-20 and PVP K-30 in different ratios ( 9:1 (Formula I); 8:2 (Formula II); 7:3 (Formula III)) and 6:4 (Formula IV). The moisture content was calculated as a difference between initial and final weight with respect to final weight. The homogeneity of patch surface was determined using Scanning Electron Microscope (SEM) Released test using dissolution tester were carried out in 500 mL of phosphate buffer salin pH 7.4 ± 0.05 at temperature 37 ± 0.5°C with speed of swirl 50 rpm. The concentration of sodium diclofenac released was determined using spectrophotometric method at l 276 nm. Data was analyzed by statistic programmed of SPSS using one way analysis of variance with degree of believed 95% (α = 0.05). It is concluded that the polymeric combination EC N-20 and PVP K-30 in composition 7:3 (Formula III) was the best formulation. ABSTRAK Telah dilakukan penelitian tentang optimasi sediaan transdermal patch natrium diklofenak tipe matriks. Pada penelitian ini, basis matriks mengandung natrium diklofenak dibuat dengan kombinasi polimer etilselulose (EC) N-20 dan polivinilpirolidon (PVP) K-30 dengan berbagai perbandingan yaitu 9:1 (Formula I); 8:2 (Formula II); 7:3 (Formula III)) dan 6:4 (Formula IV). Moisture content (MC) ditentukan dengan cara berat awal dikurangi berat akhir dan dibagi dengan berat akhir. Homogenitas permukaan patch ditentukan dengan menggunakan Scanning Electron Microscope (SEM). Uji pelepasan natrium diklofenak dilakukan dengan alat disolusi dan menggunakan dapar fosfat salin pH 7,4 ± 0.05 sebanyak 500,0 mL, kecepatan pengadukan 50 rpm dan percobaan dilakukan pada suhu 37 ± 0,5°C. Kadar natrium diklofenak yang terlepas ditentukan dengan metoda spektrofotometer pada panjang gelombang (l) 276 nm. Data yang diperoleh dianalisa secara statistik menggunakan program SPSS dengan derajat kepercayaan 95% (α = 0,05). Kesimpulan yang didapatkan adalah komposisi polimer EC N-20 dan PVP K-30 dengan perbandingan 7:3 (Formula III) adalah formula yang terbaik.